2019
DOI: 10.1002/ange.201910895
|View full text |Cite
|
Sign up to set email alerts
|

Selective Late‐Stage Sulfonyl Chloride Formation from Sulfonamides Enabled by Pyry‐BF4

Abstract: Reported here is a simple and practical functionalization of primary sulfonamides, by means of a pyrylium salt (Pyry-BF 4 ), with nucleophiles. This simple reagent activates the poorly nucleophilic NH 2 group in a sulfonamide, enabling the formation of one of the best electrophiles in organic synthesis: a sulfonyl chloride. Because of the variety of primary sulfonamides in pharmaceutical contexts, special attention has been focused on the direct conversion of densely functionalized primary sulfonamides by a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This result immediately suggested that this phenomenon is not restricted to activated aryl moieties but also extends to heteroaromatic substrates. Our group has recently reported on the synthesis and properties of a simple pyrylium reagent (Pyry-BF 4 , 1) and its capacity to engage certain azines in Zincke-type reactivity [25][26][27] ; although narrow in scope, the Pyry-BF 4 displayed high chemoselectivity for amino groups. Then, we envisaged that a merger of the reactivity observed in Fig.…”
Section: Deaminative Chlorination Of Aminoheterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…This result immediately suggested that this phenomenon is not restricted to activated aryl moieties but also extends to heteroaromatic substrates. Our group has recently reported on the synthesis and properties of a simple pyrylium reagent (Pyry-BF 4 , 1) and its capacity to engage certain azines in Zincke-type reactivity [25][26][27] ; although narrow in scope, the Pyry-BF 4 displayed high chemoselectivity for amino groups. Then, we envisaged that a merger of the reactivity observed in Fig.…”
Section: Deaminative Chlorination Of Aminoheterocyclesmentioning
confidence: 99%
“…When our protocol was applied to herbicide chloridazone, high yields of the dichlorinated pyridazone 24 were obtained. Even the polyaromatic and crowded acrisorcin could be converted in 9-chloroacridine (25), albeit at 36%. Importantly, fused polycyclic substrates present at the core of biologically relevant molecules such as adenine or remdesivir, were smoothly converted to their chlorinated analogues in very good yields (26 and 27).…”
Section: Deaminative Chlorination Of Aminoheterocyclesmentioning
confidence: 99%
“…Whereas alkyl pyridinium are ideal partners to generate alkyl radicals, [21–24] this reactivity remains challenging when translating it to the (hetero)aromatic amines, and polar reactivity still dominates. In this context, our group has reported the use of a cheap and bench‐stable salt, namely pyrylium tetrafluoroborate 1 , to convert −NH 2 groups from heterocyclic scaffolds in a highly chemoselective fashion through S N Ar reactions [25–28] . Yet, direct hydroxylation always eluded our efforts due to incompatibility of the nucleophilic hydroxyl source.…”
Section: Figurementioning
confidence: 99%
“… 2 In addition to their applications as photocatalysts, pyrylium salts have been used as precursors for a variety of other heterocycles, in particular N -alkylpyridinium salts (Katritzky salts), via reaction with primary amines. 3 The pyridinium moiety can act in these compounds as a leaving group in nucleophilic substitution reactions 4 or can lead to fragmentation upon single-electron reduction, generating alkyl radicals. Several methods for the single electron reduction of Katritzky salts have been recently investigated.…”
mentioning
confidence: 99%